Small extracellular vesicles released from germinated kiwi pollen (pollensomes) present characteristics similar to mammalian exosomes and carry a plant homolog of ALIX - Suanno, Chiara; Tonoli, Elisa; Fornari, Enzo; Savoca, Maria P.; Aloisi, Iris; Parrotta, Luigi; Faleri, Claudia; Cai, Giampiero; Coveney, Clare; Boocock, David J.; Verderio, Elisabetta A. M.; Del Duca, Stefano (Frontiers in Plant Science, 2023)
In the last decade, it has been discovered that allergen-bearing extracellular nanovesicles, termed “pollensomes”, are released by pollen during germination. These extracellular vesicles (EVs) may play an important role in pollen-pistil interaction during fertilization, stabilizing the secreted bioactive molecules and allowing long-distance signaling. However, the molecular composition and the biological role of these EVs are still unclear. The present study had two main aims: (I) to clarify whether pollen germination is needed to release pollensomes, or if they can be secreted also in high humidity conditions; and (II) to investigate the molecular features of pollensomes following the most recent guidelines for EVs isolation and identification. To do so, pollensomes were isolated from hydrated and germinated kiwi (Actinidia chinensis Planch.) pollen, and characterized using imaging techniques, immunoblotting, and proteomics. These analyses revealed that only germinated kiwi pollen released detectable concentrations of nanoparticles compatible with small EVs for shape and protein content. Moreover, a plant homolog of ALIX, which is a well-recognized and accepted marker of small EVs and exosomes in mammals, was found in pollensomes. The presence of this protein, along with other proteins involved in endocytosis, is consistent with the hypothesis that pollensomes could comprehend a prominent subpopulation of plant exosome-like vesicles.